2003
DOI: 10.1117/12.463087
|View full text |Cite
|
Sign up to set email alerts
|

Optical and fluorescence properties of corn leaves from different nitrogen regimes

Abstract: The important role of nitrogen (N) in limiting or enhancing vegetation productivity is relatively well understood, although the interaction of N with other environmental variables in natural and agricultural ecosystems needs more study. In 2001, a suite of optical, fluorescence, and biophysical measurements were collected on leaves of corn (Zea Mays L.) from field plots provided four N fertilizer application rates: 20%, 50%, 100% and 150% of optimal N levels. Two complementary sets of high-resolution (< 2 nm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…The results presented in Figures 2-6 are in agreement with those of other experimental researches [8,12] on plants under nitrogen stress and soil pollution using a fluorescence excitation source at the wavelength of 532 nm.…”
Section: Fluorescence Spectra Of Watercress In Stress State Caused Bysupporting
confidence: 90%
See 1 more Smart Citation
“…The results presented in Figures 2-6 are in agreement with those of other experimental researches [8,12] on plants under nitrogen stress and soil pollution using a fluorescence excitation source at the wavelength of 532 nm.…”
Section: Fluorescence Spectra Of Watercress In Stress State Caused Bysupporting
confidence: 90%
“…Fluorescence analysis is a widely used high-sensitivity method that is applied in many scientific and technical fields. A viable application of the technique is the analysis of plant state [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. External factors can cause plants stress and make their growth abnormal.…”
Section: Introductionmentioning
confidence: 99%
“…NPQ and chlorophyll fluorescence emission are considered as direct indicators of photosynthetic activities and physiological stress when plants are under sub-optimal environmental conditions [28,53,59,80,[90][91][92][93] such as low water availability [81,[93][94][95], unfavorable temperatures [96,97], nutrients [98][99][100][101], and salinity [102,103]. Consequently, many studies have utilized the spectral indices, PRI and SIF retrievals, as indicators of stress and down-regulation of LUE and GPP [29,50,51,65,82,92,[104][105][106][107]. Our results lend support to those reported from previous studies that demonstrated that PRI and SIF retrievals were correlated to two important protective mechanisms (NPQ and chlorophyll fluorescence emissions), discarding excess absorbed solar radiation that could not be used in photosynthesis [3,29,54].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies demonstrated the possibility to measure SIF at certain wavelengths on ground Rascher et al, 2009), from airborne platforms (Damm et al, 2014;Guanter et al, 2007;Zarco-Tejada, Gonzalez-Dugo, & Berni, 2012), and from satellites (Frankenberg et al, 2011;Guanter et al, 2014;Joiner et al, 2013). Recent research demonstrated SIF being sensitive to changes in photosynthesis, showing strong links to GPP at the level of leaves (Meroni et al, 2008;Middleton et al, 2002), plants Rossini et al, 2010), canopies (Zarco-Tejada, Morales, Testi, & Villalobos, 2013), and ecosystems (Frankenberg et al, 2011;Guanter et al, 2012).…”
Section: Introductionmentioning
confidence: 98%